2022
DOI: 10.3389/fmicb.2022.983660
|View full text |Cite
|
Sign up to set email alerts
|

The influence of species identity and geographic locations on gut microbiota of small rodents

Abstract: Although the correlation between gut microbiota, species identity and geographic locations has long attracted the interest of scientists, to what extent species identity and geographic locations influence the gut microbiota assemblages in granivorous rodents needs further investigation. In this study, we performed a survey of gut microbial communities of four rodent species (Apodemus agrarius, A. peninsulae, Tamias sibiricus and Clethrionomys rufocanus) distributed in two areas with great distance (> 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
4
7
0
Order By: Relevance
“…Host species account for less variance in the gut microbiota of rats in comparison to biogeography factors (Linnenbrink et al, 2013;Baxter et al, 2015;Teng et al, 2022) with host species, suggesting commonalities in gut microbiota among species (Nagpal et al, 2018;Weinstein et al, 2021;10.3389/fmicb.2023.1258775 Frontiers in Microbiology 12 frontiersin.org Doms et al, 2022). However, the host environment and genetics interact to shape phylosymbiosis (Griffiths et al, 2019;Wang et al, 2022). The core bacteria identified in this study may have important effects on health and fitness.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Host species account for less variance in the gut microbiota of rats in comparison to biogeography factors (Linnenbrink et al, 2013;Baxter et al, 2015;Teng et al, 2022) with host species, suggesting commonalities in gut microbiota among species (Nagpal et al, 2018;Weinstein et al, 2021;10.3389/fmicb.2023.1258775 Frontiers in Microbiology 12 frontiersin.org Doms et al, 2022). However, the host environment and genetics interact to shape phylosymbiosis (Griffiths et al, 2019;Wang et al, 2022). The core bacteria identified in this study may have important effects on health and fitness.…”
Section: Discussionmentioning
confidence: 66%
“…They showed that the environment has a greater effect than host species identity (Teng et al, 2022). In addition, the gut microbiome diversity of many rodent species is thought to be influenced by host genetic and geographic differences (Wang et al, 2022). Geographic trends in microbiota composition in human and mouse gut microbiomes have been recognized (Linnenbrink et al, 2013;Rehman et al, 2016;Suzuki et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…4,5,6,7,8,9,10 . The diversity of the human gut microbiome in both healthy 11,12,13 and sick 13 individuals is greatly in uenced by the geographic location and dietary history of a population. The gut microbiota of a healthy adult human, are dominated by two bacterial phyla Firmicutes and Bacteroidetes.…”
Section: Introductionmentioning
confidence: 99%
“…Host genetic background can also have substantial implications for microbiota composition (Zhernakova et al, 2016), though its role remains unexplored in most species given the need for large cohorts for which both genomic and microbiota data are available. While such datasets have recently been analysed for humans (Awany et al, 2019;Goodrich et al, 2016;Hall et al, 2017;Ishida et al, 2020) and some animal species (including rodents [Doms et al, 2022;Suzuki et al, 2019;Wang et al, 2015Wang et al, , 2022, ruminants and poultry [see Ryu & Davenport, 2022] and even wild baboons [Grieneisen et al, 2021]), to our knowledge a study on the relationship between the microbiota and host genome has not yet been undertaken for any threatened wildlife. Such information should help inform future efforts at microbiome engineering of threatened species (e.g.…”
Section: Introductionmentioning
confidence: 99%